2013
DOI: 10.21726/rsbo.v9i1.959
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between electronic and radiographic method for the determination of root canal length in primary teeth

Abstract: There are few researches in literature that mention the use of the apex locator in deciduous teeth and working length is obtained through radiographies. Objective: The purpose of this research was to compare the radiographic and the electronic method to obtain the working length in deciduous molars. Material andmethods: Twelve molar teeth were used. The specimens in the visual method had their root length measured through the passive insertion of a 10 K-file with a silicone stop within root canal until its tip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The first stage of screening produced 25 results that were all retrieved and assessed for eligibility. Fourteen articles were included in the qualitative analysis (4, 5, 7, 14–24), while 11 were excluded for the following reasons: five articles described insufficient sample size (25–29), two studies reported unclear data (30, 31), three studies had unproper study design (a commentary (32) and two in vitro (33, 34) studies) and a single study reported duplicated data (35).…”
Section: Resultsmentioning
confidence: 99%
“…The first stage of screening produced 25 results that were all retrieved and assessed for eligibility. Fourteen articles were included in the qualitative analysis (4, 5, 7, 14–24), while 11 were excluded for the following reasons: five articles described insufficient sample size (25–29), two studies reported unclear data (30, 31), three studies had unproper study design (a commentary (32) and two in vitro (33, 34) studies) and a single study reported duplicated data (35).…”
Section: Resultsmentioning
confidence: 99%